Penerapan Model Kooperatif Tipe Group Investigation untuk Meningkatkan Hasil Belajar Siswa Pada Pokok Bahasan Usaha dan Energi - Rahmati, Rahmati; Arusman, Arusman (Jurnal Kolaborasi Akademika, 2026)
This study aims to determine the improvement of learning outcomes and to determine the activities of teachers and students towards the application of the cooperative learning model of the group investigation type on the concept of work and energy. The subjects of the study were students of class VIII SMPN 1 Jaya, Aceh Jaya Regency. The instruments in this study were student learning test sheets and observation sheets of teacher and student activities. The data obtained in this study were analyzed using percentage statistics. The results showed that the increase in student learning outcomes from 50% in cycle I to 64.51% in cycle II and to 93.54% in cycle III. The average score of teacher activity showed that in cycle I it was good, then in cycle II it was good, and in cycle III it was in the very good category. Furthermore, the average score of student activity showed that in cycle I it was good, then in cycle II it was good, and in cycle III it was also in the good category.